The Influence Of Job Placement, Work Experience And Career Development On Employee Performance At The South Sumatra Provincial Pu Bina Marga And Spatial Planning Office - Santoso, Teguh; Fauziah Afriyani; Try Wulandari (LPPM Universitas Negeri Jakarta, 2025)
This research seeks to examine the impact of job placement, work experience, and career development on employee performance at the Office of Public Works Bina Marga and Spatial Planning of South Sumatra Province. “The research used descriptive quantitative methodologies and sampling procedures, using simple random sampling based on the Slovin formula, with a sample size of 130 respondents drawn among 192 ASN workers. Multiple linear regression was used for data analysis. The findings indicated that job placement, work experience, and career advancement each had a favourable and substantial influence on employee performance. Of these characteristics, career advancement has the most significant impact. The three factors concurrently have a substantial impact on employee performance. The correlation coefficient signifies a robust association, but the coefficient of determination reveals that the majority of the variability in employee performance is accounted for by these three components, with a little proportion affected by external variables not included in this research.